VIRTUAL REALITY AND AUGMENTED REALITY IN MEDICAL SIMULATION (International journal of artificial intelligence, 2025)
The rapid advancement of information technologies has significantly transformed medical education and training. Among these innovations, Virtual Reality (VR) and Augmented Reality (AR) have emerged as powerful tools for enhancing medical simulations. These technologies allow medical students and healthcare professionals to experience realistic, interactive, and immersive training environments without risk to real patients. VR provides a fully computer-generated 3D environment that replicates surgical procedures, anatomy visualization, and emergency response training, while AR overlays digital information onto the real world, enhancing hands-on learning. The integration of VR and AR in medical education improves learning efficiency, clinical decision-making, and psychomotor skills. Moreover, these technologies help reduce training costs and improve accessibility to complex medical scenarios. However, challenges remain, including high implementation costs, technical limitations, and the need for standardized evaluation frameworks. Overall, VR and AR are transforming traditional medical education by providing a safe, effective, and interactive learning experience for the next generation of healthcare professionals.